الإدارة المتكاملة للمياه الجوفية الملوثة بالنترات في سهل عكار طرطوس - وزان, أحمد (Latakia University Journal -Engineering Sciences Series, 2016)
يعد تلوث المياه الجوفية بالنترات مشكلة شائعة في العديد من دول العالم وبخاصة الزراعية منها حيث ينشأ التلوث في هذه البلدان بشكل أساسي من الاستخدام الزائد للتسميد في المناطق الزراعية ومن النفايات الصناعية والصرف الصحي وروث الحيوانات، وأيضا" من التثبيت الجوي للنتروجين بواسطة النباتات، بالإضافة إلى مركبات النتروجين التي تنشأ بفعل بعض الصناعات وانبعاثات السيارات وتترسب على الأرض بشكل مواد صلبة. وتعد النترات من المركبات المسرطنة والخطرة على الصحة البشرية إذا ما وجدت بتراكيز مرتفعة، وتأتي هذه الخطورة من تحول النترات الممتص إلى نتريت بفعل بكتريا خاصة في البطن والذي يسبب بدوره ما يعرف بالميثموغلوبينيميا لدى الرضع والحوامل (مرض ازرقاق الرضع ) كما يمكن أن يسبب سرطان المعدة لدى البالغين عبر تفاعله مع الأمينات والأميدات في البطن مشكلاً مواد مسرطنة (النتروزأميدات والنترزوأمينات)، لذلك يجب تطبيق أسس الإدارة المتكاملة للمياه الجوفية في منطقة الدراسة والمحافظة على مستويات منخفضة للنترات في المياه الجوفية المستخدمة للشرب وللري . The contamination of groundwater with nitrates is a common problem in many countries of the world, especially the agricultural ones where the pollution originates in these countries mainly from the use of excessive fertilization in agricultural areas, industrial waste, sewage, animal dung, and the "installation of air nitrogen by plants, the nitrogen compounds that arise due to some industries and vehicle emissions which are deposited on the ground in solids. The nitrate compounds are carcinogens and hazardous to human health If they were in high concentrations. The risk of this turning into nitrite nitrate uptake by the bacteria, especially in the abdomen which in turn causes what is known as Balmithmoglubenemea in infants and pregnant women (Infant disease blueness). It can also cause stomach cancer in adults through its interaction with amines and amides in the abdomen, forming carcinogens (Alntrozzomedat and Alentrzoaminat). Therefore, you must apply the foundations of the integrated management of groundwater in the study area to maintain low levels of nitrate in groundwater used for drinking and irrigation.